Comparisons of fascio‐cutaneous anterolateral thigh and sandwich fascial ALT free flap in the distal extremity reconstruction. Issue 4 (14th September 2019) - Cherubino, Mario; Stocco, Chiara; Ronga, Mario; Tamborini, Federico; Maggiulli, Francesca; Di Giovanna, Danilo; Campisi, Corrado; Di Summa, Pietro; Valdatta, Luigi
Abstract: Introduction: The anterolateral thigh (ALT) flap is considered a workhorse reconstructive option; however, it is encumbered by its bulkiness that can result in poor final outcome and need for revision surgery. The aim of the present study was to compare the standard cutaneous ALT free flap and sandwich fascial ALT (SALT) free flap, raised harvesting between the Scarpa's fascia and the crural fascia, for distal extremity soft tissue reconstruction, including pre‐ intra‐ and post‐operative considerations and outcomes. Patients and methods: A retrospective review of medical records from 2013 to 2018 of 24 patients who underwent distal extremity reconstruction with standard fascio‐cutaneous ALT flap (13 patients) and SALT flap (11 patients) was performed. The mean defect dimensions were 12 × 6.5 cm in group 1 and 12 × 6 in group 2. Surgical outcomes and quality of life were assessed ( through the upper extremity functional scale and the lower extremity functional scale questionnaires. Results: The mean flap dimensions were 13.1 × 7.1 in group 1 and 14.1 × 7.8 in group 2, the overall flap success rate was 100% (one microvascular venous thrombosis occurred in group 1), no statistically significant difference was recorded regarding microvascular thrombosis (one patient in group p = .369) and infections (one patient in group 1, p = .36) while a statistically significant difference was presence regarding the number of secondary/debulking procedures (6 patients vs. 0) ( p = .0076) and the quality of life perception showed an overall better perception in group 2 with statistical significant difference ( p = .03). Conclusion: The SALT flap represents a valid option, as showed through our preliminary data, when a thin and robust reconstruction is required when dealing with distal extremities soft tissue reconstruction.